Counterinsurgency campaigning and national security transformation : lessons from the Eelam war. - Bhatna Sanjaya Colonne. (2008)
Examines insurgency and counterinsurgency (COIN) strategy vis-a-vis the ‘Eelam War’ in Sri Lanka and reveals the fact that overreaction by the state and its inability to adhere to principles of COIN could exacerbate the crisis in favour bf the insurgents.